Proteolytic activity of excretory/secretory products of Cochliomyia hominivorax (Diptera: Calliphoridae) - Giglioti, Rodrigo [UNESP]; Guimarães, Semíramis [UNESP]; Oliveira-Sequeira, Teresa C.G. [UNESP]; David, Erica B. [UNESP]; Brito, Luciana G.; Huacca, Maribel E.F.; Chagas, Ana C.S.; Oliveira, Márcia C.S. (FapUNIFESP (SciELO), 2016)
The protein profiles and proteolytic activity of the excretory secretory products (E/SP) of the first (L1), second (L2) and third (L3) larval stages of Cochliomyia hominivorax were studied in the laboratory. Analysis on the E/SP protein profile was carried out using polyacrylamide gel containing sodium dodecyl sulfate (SDS-PAGE). The E/SP of each larval stage (L1, L2 and L3) treated with protease inhibitors, containing 30μg, 40μg and 50μg of protein, was applied to the 10% polyacrylamide gel. The proteolytic activity of the crude E/SP was analyzed in gels copolymerized with gelatin and by colorimetric assays using azocasein as a substrate, with the characterization of the proteases using synthetic inhibitors. Different protein profiles were observed for the larval instars, with L1 presenting the most complex profile. Nevertheless, various protein bands were observed that were common to all the larval instars. The E/SP of all the instars showed proteolytic activity on gelatin, evidenced by proteolysis zones, predominantly with apparently higher molecular masses in L1, while for L2 and L3 the proteolysis zones could also be observed in regions with lower masses. Tests with protease inhibitors using gelatin as substrate showed that the E/SP of larvae were mainly composed of serine proteases. Additionally, inhibition was observed in L2 E/SP treated previously with EDTA, an inhibitor of metalloproteases. The assays with azocasein revealed a gradual increase of proteolytic activity on this substrate with larval development progress, with the strongest inhibitions being observed after treatments with 3,4-dichloroisocoumarin (DCI) for E/SP of L1, L2 and L3. These results suggest that C. hominivorax larvae produce different proteases, a fact that can be related to the parasite's vital processes for survival, such as penetration into the host's tissues and nutrition during the larval stage.
Keywords: Calliphoridae; Cochliomyia hominivorax; Diptera; Myiasis; Proteases; Proteolytic activity; Screwworm fly